Penerapan Model Problem Based Learning terhadap Aktivitas Belajar Peserta Didik pada Mata Pelajaran IPS - Yesmita, Yana; Rahayu, Sri; Harisnawati, Harisnawati (Darul Yasin Al Sys, 2023)
In teaching and learning activities at SMP N 1 Sungai Rumabai, teachers who teach social studies still use the lecture method, group discussions, and question and answer so that this method will make students feel less bored when the teacher explains the material being taught. Therefore this study aims to be able to analyze the application of the problem-based learning model to the learning activities of students in social studies class VIIb at SMP N 1 Sungai Rumbai. The theory used is behavioristic theory, from B.F. Skinner. This research method uses a quantitative approach with a descriptive type. Techniques for collecting data are observation and document study. Sampling used a porposive/sampling technique with a total sample of 29 students. The data for this study were obtained from daily tests in the form of 25 multiple choice questions. Data analysis uses percentage analysis, namely in a clasical manner. The results of the research on the application of the problem-based learning learning model to the learning activities of students in class VIIb as much as 2 teacher preparation meetings before implementing PBL (1) The teacher prepares the flow of learning objectives (2) The teacher determines the theme of each group in teaching and learning activities (KBM) For 2 meetings (3) The teacher divides students into each group in group discussions (4) The teacher prepares media that is used to support teaching and learning activities such as laptops, infocus, pictures, and blackboards. Application of the problem-based learning model at the first teacher meeting begins (KBM) by greeting, praying and checking student attendance, the main activities (1) determine the theme (2) divide students into groups (3) and present the results of group discussions after that draw conclusions. so from the results of the test tests used it can be concluded that there were 25 students (77%) the results of the learning activities of students in good or complete achievement of KKM, namely, 73 so that there was an effect of applying the problem-based learning model to student learning activities.